Between the line: the semiotics of everyday life in the Brazil-Uruguay borderlands - Simi, Gianlluca (2019)
The border is primarily a polysemic sign, whose meanings are constant-ly (re)created in the everyday in accordance with the various intentions that individuals might find convenient to enunciate. It does not, there-fore, have a universally fixed meaning, especially to those whose lives are permeated by its wavering between a dominant presence and a per-missive absence. This thesis builds on the fieldwork in Chuy, a twin town in the borderlands between Brazil and Uruguay, where there is an in-tense friction between the border as a strategy for division and control as well as an everyday landscape feature that is tactically experienced in terms of its openness and fluidity. Drawing on responses given by 426 local residents, on nine in-depth interviews, and on field notes, a topo-graphic map of meanings and uses assigned to the border in the region is sketched with the following question in mind: what does it mean to live by the border? The semiotic approach adopted in this thesis prefers to look at the border in its utter incorporation into everyday life, from which the word itself comes to convey processes of signification that take into account the meanings and uses that are associated with the border in the present and in relation to the history of Chuy, located in the Neutral Fields, a buffer zone that was created by the Treaty of San Ildefonso in 1777 as an attempt to solve disputes over territory in the region by effec-tively prohibiting any contact between the outlying sides. Results sug-gest that instances of re-bordering occur as often as those of de-bordering, ultimately rejecting a totalising view of the borderlands in positive terms, as initially identified by surveys. Individuals calculate the poten-tial risks and gains of certain uses of the border, pointing to three main flows of ideas related to the border in Chuy, namely: shopping, culture, and diversity. The general conclusion of the thesis suggests that the bor-der is as meaningful as its uses, thus calling for further study into the ways in which material culture and the mobilisation of perceptions in-terrelate in open borderlands.